(untitled) (Environment & Health, 2021)
Objective: We assessed a probable role of pesticides as generalized products of plant protection means in the formation of the hormone-dependent oncological incidence in the population. Materials and methods: In the work we analyzed the territorial features of plant protection chemicals use and the population endocrine cancer incidence data (breast and thyroid cancer in men and women, prostate cancer in men, ovarian and uterine cancer in women, calculated according to the Ukrainian standard) based on the materials from National Cancer Registry of Ukraine. Results: Territorial dependences between gross indicators of the used chemical protection means, rates of their increase in the agriculture and indicators of the population endocrine cancer incidence were revealed. The most intensive growth was shown to be observed in the regions with a predominantly agricultural mode of production. The performed linear regression analysis confirmed a direct strong correlation between the volume of pesticide at the household use and the incidence of ovarian cancer (r = 0.89; p>0.01) and prostate cancer (r = 0.87; p>0.01). Conclusion: Although the results of the analytical consideration of the problem and the data of linear-regression analysis indicate a possible role of pesticides in the induction of endocrine cancer, further research is needed in this field. In the future, it is important to consider the problem by classes and groups of pesticides with the possibility of the approach to the definition of the effect mechanisms.